North Carolina Macular Dystrophy: Phenotypic Variability and Computational Analysis of Disease-Associated Noncoding Variants - Green, David J.; Lenassi, Eva; Manning, Cerys S.; McGaughey, David; Sharma, Vinod; Black, Graeme C.; Ellingford, Jamie M.; Sergouniotis, Panagiotis I. (Investigative ophthalmology & visual science, 2021)
North Carolina macular dystrophy (NCMD) is an autosomal dominant, congenital disorder affecting the central retina. Here, we report clinical and genetic findings in three families segregating NCMD and use epigenomic datasets from human tissues to gain insights into the effect of NCMD-implicated variants.PurposeNorth Carolina macular dystrophy (NCMD) is an autosomal dominant, congenital disorder affecting the central retina. Here, we report clinical and genetic findings in three families segregating NCMD and use epigenomic datasets from human tissues to gain insights into the effect of NCMD-implicated variants.Clinical assessment and genetic testing were performed. Publicly available transcriptomic and epigenomic datasets were analyzed and the activity-by-contact method for scoring enhancer elements and linking them to target genes was used.MethodsClinical assessment and genetic testing were performed. Publicly available transcriptomic and epigenomic datasets were analyzed and the activity-by-contact method for scoring enhancer elements and linking them to target genes was used.A previously described, heterozygous, noncoding variant upstream of the PRDM13 gene was detected in all six affected study participants (chr6:100,040,987G>C [GRCh37/hg19]). Interfamilial and intrafamilial variability were observed; the visual acuity ranged from 0.0 to 1.6 LogMAR and fundoscopic findings ranged from visually insignificant, confluent, drusen-like macular deposits to coloboma-like macular lesions. Variable degrees of peripheral retinal spots (which were easily detected on widefield retinal imaging) were observed in all study subjects. Notably, a 6-year-old patient developed choroidal neovascularization and required treatment with intravitreal bevacizumab injections. Computational analysis of the five single nucleotide variants that have been implicated in NCMD revealed that these noncoding changes lie within two putative enhancer elements; these elements are predicted to interact with PRDM13 in the developing human retina. PRDM13 was found to be expressed in the fetal retina, with greatest expression in the amacrine precursor cell population.ResultsA previously described, heterozygous, noncoding variant upstream of the PRDM13 gene was detected in all six affected study participants (chr6:100,040,987G>C [GRCh37/hg19]). Interfamilial and intrafamilial variability were observed; the visual acuity ranged from 0.0 to 1.6 LogMAR and fundoscopic findings ranged from visually insignificant, confluent, drusen-like macular deposits to coloboma-like macular lesions. Variable degrees of peripheral retinal spots (which were easily detected on widefield retinal imaging) were observed in all study subjects. Notably, a 6-year-old patient developed choroidal neovascularization and required treatment with intravitreal bevacizumab injections. Computational analysis of the five single nucleotide variants that have been implicated in NCMD revealed that these noncoding changes lie within two putative enhancer elements; these elements are predicted to interact with PRDM13 in the developing human retina. PRDM13 was found to be expressed in the fetal retina, with greatest expression in the amacrine precursor cell population.We provide further evidence supporting the role of PRDM13 dysregulation in the pathogenesis of NCMD and highlight the usefulness of widefield retinal imaging in individuals suspected to have this condition.ConclusionsWe provide further evidence supporting the role of PRDM13 dysregulation in the pathogenesis of NCMD and highlight the usefulness of widefield retinal imaging in individuals suspected to have this condition.